ISLAMIC VALUE-BASED SPORTS LEARNING MANAGEMENT IN SHAPING STUDENTS' DISCIPLINARY CHARACTER - Toi Akbari (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to analyze how sports learning management, integrated with Islamic values, contributes to the formation of students' disciplinary character. Sports are often viewed merely as physical activities; however, with proper management based on Islamic values, they become an effective medium for character education. The research method employed is descriptive qualitative through literature review and field observations. The focus of the study includes instructional planning that incorporates sports ethics (adab), implementation emphasizing the teacher's role model (uswatun hasanah), and behavioral evaluation based on principles of honesty and responsibility. The findings indicate that structured learning management—ranging from habituating prayer times during practice intervals to strict adherence to fair play rules—significantly enhances student discipline. In conclusion, the integration of Islamic values in sports management creates an educational ecosystem that not only strengthens the physical aspect but also builds moral integrity and systemic compliance in students.